2014
DOI: 10.1074/jbc.a112.356535
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits Rift Valley fever virus replication in human cells.

Abstract: PAGE 33201:The curcumin nanoparticle binding assay described failed to indicate that 1 ml of chitosan (5 mg/ml stock at pH 5) was combined with PEG, curcumin, and phosphate-buffered saline in the first step and that hydrolyzed tetramethylorthosilicate (TMOS) was used, not trimethoxysilane. This protocol was based on the platform developed by Friedman et al. (Friedman, A. J., Han, G., Navati, M. S., Chacko, M., Gunther, L., Alfieri, A., and Friedman, J. M. (2008) Sustained release nitric oxide releasing nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…In cases of VACV, HSV-1 and KSHV infections viral proteins bind to IKKb to inhibit subsequent phosphorylation of IjBa (Seo et al, 2004;Jin et al, 2011;Ember et al, 2012;Le Negrate, 2012). Interestingly, in RVFV and VEEV infections, viral proteins themselves maybe potentially phosphorylated by IKKb to enhance viral replication and increase pathogenesis (Narayanan et al, 2012;Amaya et al, 2014). We and others have reported that by depleting IKKb in the host cell viral replication is decreased (Gregory et al, 2004;Li et al, 2013;Amaya et al, 2014), which serves as an indicator that this host protein is required for viral replication.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In cases of VACV, HSV-1 and KSHV infections viral proteins bind to IKKb to inhibit subsequent phosphorylation of IjBa (Seo et al, 2004;Jin et al, 2011;Ember et al, 2012;Le Negrate, 2012). Interestingly, in RVFV and VEEV infections, viral proteins themselves maybe potentially phosphorylated by IKKb to enhance viral replication and increase pathogenesis (Narayanan et al, 2012;Amaya et al, 2014). We and others have reported that by depleting IKKb in the host cell viral replication is decreased (Gregory et al, 2004;Li et al, 2013;Amaya et al, 2014), which serves as an indicator that this host protein is required for viral replication.…”
Section: Resultsmentioning
confidence: 99%
“…Rift valley fever virus (RVFV) is a negative sense ssRNA virus that belongs to the family Bunyaviridae. This arbovirus is a select agent and a known agricultural pathogen that infects livestock and humans (LaBeaud et al, 2010;Boshra et al, 2011;Narayanan et al, 2012). We have recently shown that the attenuated strain of RVFV, MP-12, induced phosphorylation of p65 and IjBa via the canonical NF-jB cascade (Narayanan et al, 2012).…”
Section: Rna Viruses and Ikkbmentioning
confidence: 99%
See 2 more Smart Citations
“…To create curc-np, we modified our previously described sol-gel-based protocol [31,32]. Tetramethyl orthosilicate (TMOS) was hydrolyzed by adding HCl, followed by sonication on ice.…”
Section: Synthesis Of Curcumin-nanoparticlesmentioning
confidence: 99%